UPAYA PENINGKATAN PEMBELAJARAN GERAKDASAR TOLAK PELURU DENGAN PENDEKATANBERMAIN SISWA KELAS V SD NEGERI 1 DEMANGSARIAYAH KABUPATEN KEBUMEN - Gregorius Kristiyono - Eddy Purnomo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractThis study is concerned about determining the increase of learning basic motionsof shot put through such an approachas playing with the fifth graders of SD Negeri 1 Demangsari Ayah Kebumen. This is class action researchconsisting ofthree cycles, in which the subjects were 12 students of the fifth graders of SD Negeri 1 Demangsari Ayah Kebumen.The object of the research is the improvement of learning basic motionsof shot put which is measured thriugh thestudents’ learning seriousness (interest, motivation and participation) and the performance of the students. Theinstrument employed in this research was a classroom observation, questionnaires, and tests that measured theirperformance of the basic motions of shot put. The results show that through such an approach as playingstudents’basic-motions learning of shot put, which is measured through their seriousness of learning (interest, motivation andparticipation) and the performance of the basic motions of shot put of the fifth graders of SDN 1 Demangsari AyahKebumen can actually be enhanced. Based on the data of the test results of basic-motion performance of shot puton the first cycle, the average score of their performance is 69.18: students who completed their study were 41.67%and the students who did not were 58.33%. On the second cycle, the average score of their performance is 72.57:students who completed their study were 75% and students who did not were 25%. On the third cycle, the averagescore of the students’ performance is 77.00, and all of them completed their study or 100% of them get the scoreabove the fixed minimum completeness of criteria: that is 70.Keywords: learning improvement, basic motion of shot put, playing approachAbstrakPenelitian ini dilatarbelakangi oleh permasalahan masih rendahnya kualitas pembelajaran pendidikan jasmaniterutama dalam materi tolak peluru pada siswa kelas V SD Negeri 1 Demasngsari, Ayah, Kabupaten Kebumen.Penelitian ini bertujuan untuk mengetahui peningkatan pembelajaran gerak dasar tolak peluru dengan pendekatanbermain siswa kelas V SD Negeri 1 Demangsari Ayah Kebumen. Penelitian ini merupakan penelitian tindakan kelasyang terdiri atas 3 siklus, setiap siklus 1 kali pertemuan, setiap pertemuan 70 menit. Subjek penelitian adalah siswakelas V SD Negeri 1 Demangsari Ayah Kebumen, yang berjumlah 12 siswa. Objek penelitian adalah peningkatanpembelajaran gerak dasar tolak peluru yang diukur dengan kesungguhan belajar siswa (minat, motivasi dan partisipasi)dan unjuk kerja siswa. Instrumen yang digunakan adalah observasi kelas, angket, dan tes unjuk kerja gerak dasartolak peluru. Hasil penelitian menunjukkan bahwa melalui pendekatan bermain dapat meningkatkan pembelajarangerak dasar tolak peluru, diukur dengan kesungguhan belajar (minat, motivasi dan partisipasi) dan unjuk kerjaketerampilan gerak dasar tolak peluru siswa kelas V SD Negeri 1 Demangsari Ayah Kebumen. Berdasarkan datahasil tes unjuk kerja keterampilan gerak dasar tolak peluru pada siklus pertama, rata-rata nilai unjuk kerja siswamencapai 69,18, siswa yang tuntas belajar 41,67% dan siswa yang belum tuntas 58,33%. Pada siklus kedua,rata-rata nilai unjuk kerja siswa mencapai 72,57, siswa yang tuntas belajar 75% dan siswa yang belum tuntas25%. Pada siklus ketiga, rata-rata nilai unjuk kerja siswa mencapai 77,00, semua siswa tuntas belajar atau 100%di atas nilai kriteria ketuntasan minimal yang ditetapkan yaitu 70. Kata Kunci: Pembelajaran, gerak dasar tolak peluru, pendekatan bermain.